Leading Through Change : 2020 - Domenick J Pinto (Academic Chairpersons Conference Proceedings, 2020)
Having served as department chair and school director for 31 years, I have witnessed a tremendous evolution in the role of chair as economic, social and student climates have changed. My session will summarize collected data from chairs of departments of various sizes and types in order to discuss and understand better our ever changing role as we see responsibilities of delegating, leading change, creative budgeting and fundraising, grant writing and managing conflict become vital to our positions
Keywords: peers; leadership; administration; communication; faculty